The fourth industrial revolution and the future of work: Reasons to worry and policies to consider. - Goldsmith, Arthur H.; Casey, James F. (Southern Economic Journal, 2024)
A striking feature of the contemporary U.S. economy is the widespread adoption of technologies associated with the 4th Industrial Revolution (IR) including sensors, industrial robotics, artificial intelligence, and machine learning. Empirical work investigating the labor market impacts of 4th IR technological advances reveals they are skill‐biased, primarily advancing job opportunities for those with high levels of formal of education, unlike prior industrial revolutions that were skill neutral. This paper explains how the 4th IR has fostered job polarization, greater technological unemployment, and increasing wage inequality. Moreover, we delineate why these developments are worrisome and likely to expand over time. We assert that policy intervention to promote reinstatement of technologically unemployed persons is warranted, because displacement of labor caused by automation creates negative externalities. Consequently, we provide an example of how tax policies could be used to curtail technological unemployment—without creating hurdles for the adoption of 4th IR innovations. We advance and describe a new, innovative way, for fiscal policy to foster employment opportunities for those at greatest risk of job loss through automation. The initiative entails government subsidies to promote the provision and acquisition of skill certificates that employers view as complementary with 4th Industrial Revolution Technologies.